Lower Blood Loss with Bicruciate-Retaining Total Knee Arthroplasty Compared with Bicruciate-Stabilized Total Knee Arthroplasty - Kozu, Takashi; Iriuchishima, Takanori; Ryu, Keinosuke; Nakanishi, Kazuyoshi (The Journal of Knee Surgery, 2024)
Total knee arthroplasty (TKA) is a common surgical procedure to treat end-stage knee osteoarthritis. This study compared blood loss volume and other clinical outcomes between bicruciate-retaining (BCR) and bicruciate-stabilized (BCS) TKA. Ninety-seven participants who underwent unilateral TKA were enrolled. The BCS-TKA and BCR-TKA groups comprised 78 and 19 participants, respectively. Blood loss was calculated using preoperative and postoperative hematocrit values, height, weight, and sex. Measurements were taken immediately after surgery, on days 1 and 7, and total blood loss was calculated up to day 7. Operation time, range of motion at 7 and 14 days postoperatively, blood transfusion requirement, and postoperative complications such as infection, hematoma, and deep vein thrombosis were compared between the groups. Blood loss was comparable between groups at all time points (125.7 vs. 105.4 mL, 57.9 vs. 43.5 mL, and 68.2 vs. 41.7 mL for immediate, day 1, and day 7 postoperatively, respectively; all p > 0.05) except for total blood loss, which was significantly lower in the BCR group compared with the BCS group (190.7 vs. 251.1 mL; p < 0.05). The BCR group also had a longer operation time than the BCS group (131.2 vs. 112.4 minutes; p < 0.05). No other significant differences were observed in other outcomes. Total blood loss up to 7 days postoperatively was significantly lower in the BCR group than in the BCS group despite a longer operation time. This may be attributed to the reduced bone resection and greater soft tissue preservation, including the anterior cruciate and posterior cruciate ligaments, in the BCR technique.
Keywords: total knee arthroplasty; bicruciate retaining; bicruciate stabilized; blood loss volume; osteoarthritis